2021
DOI: 10.1177/15459683211029235
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Short-Term Intensive Language–Action Therapy in Chronic Aphasia: A 1–2 year Follow-Up Study

Abstract: Background. Intensive aphasia therapy can improve language functions in chronic aphasia over a short therapy interval of 2–4 weeks. For one intensive method, intensive language–action therapy, beneficial effects are well documented by a range of randomized controlled trials. However, it is unclear to date whether therapy-related improvements are maintained over years. Objective. The current study aimed at investigating long-term stability of ILAT treatment effects over circa 1–2 years (8–30 months). Methods. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In our meta‐analysis, the influence of time post‐onset of stroke was seen only for IPD, not for RCT data. We submit two potential reasons for this differential finding: first, it may be a statistical artifact (fewer data points in the RCT category); second, substantial heterogeneity may exist among post‐stroke recovery trajectories, which does not “subtract out” during a treatment‐versus‐control comparison 33 . The latter conjecture would require consolidation by behavioral data in analogy to neurobiological models of language recovery 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our meta‐analysis, the influence of time post‐onset of stroke was seen only for IPD, not for RCT data. We submit two potential reasons for this differential finding: first, it may be a statistical artifact (fewer data points in the RCT category); second, substantial heterogeneity may exist among post‐stroke recovery trajectories, which does not “subtract out” during a treatment‐versus‐control comparison 33 . The latter conjecture would require consolidation by behavioral data in analogy to neurobiological models of language recovery 34 …”
Section: Discussionmentioning
confidence: 99%
“…8 To date, randomized controlled trial (RCT) data have confirmed the efficacy of MIT on validated outcomes in the late subacute or consolidation stage of aphasia (i.e., up to 12 months after stroke), 9 but not in the chronic stage of symptoms (i.e., more than 6-12 months after stroke). 10 From a methodological perspective, influences of spontaneous recovery are generally lower in the chronic stage of aphasia, as suggested by RCT data 11 and meta-analyses. 12 This points out the need to carefully consider the stage of symptoms post-stroke in research on MIT.…”
Section: Introductionmentioning
confidence: 99%
“…We submit two potential reasons for this differential finding: first, it may be a statistical artifact (fewer data points in the RCT category); second, substantial heterogeneity may exist among post-stroke recovery trajectories, which does not “subtract out” during a treatment-vs.-control comparison. 33 The latter conjecture would require consolidation by behavioural data, possibly incorporating Saur et al’s model of language recovery. 34…”
Section: Discussionmentioning
confidence: 99%
“…From a methodological point of view, influences of spontaneous recovery are generally lower in the chronic stage of aphasia, as suggested by RCT data 10 and meta-analyses 11 . Therefore, it is important to consider stage of symptoms post-stroke.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation